2003
DOI: 10.1124/dmd.31.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and Metabolic Fate of Atomoxetine Hydrochloride: The Role of CYP2D6 in Human Disposition and Metabolism

Abstract: ABSTRACT:The role of the polymorphic cytochrome P450 2D6 (CYP2D6) in the pharmacokinetics of atomoxetine hydrochloride [(؊)-N-methyl-␥-(2-methylphenoxy)benzenepropanamine hydrochloride; LY139603] has been documented following both single and multiple doses of the drug. In this study, the influence of the CYP2D6 polymorphism on the overall disposition and metabolism of a 20-mg dose of 14 C-atomoxetine was evaluated in CYP2D6 extensive metabolizer (EM; n ‫؍‬ 4) and poor metabolizer (PM; n ‫؍‬ 3) subjects under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 7 publications
7
132
0
2
Order By: Relevance
“…Atomoxetine is well absorbed in gastrointestinal tract and predominantly metabolized by cytochrome P4502D6 (CYP2D6). After oral administration of 20 mg twice daily in adults, the C max have been observed in the range of 160-180 ng/ml (0.55-0.62 μM) in CYP2D6 extensive metabolizers and up to 925 ng/ml (3.17 μM) in genetically deficient CYP2D6 metabolizers (Sauer et al, 2003). In our in vitro studies, atomoxetine proved to be the most potent P-glycoprotein inhibitor of all the tested agents potentially utilized to treat ADHD.…”
Section: Discussionmentioning
confidence: 78%
“…Atomoxetine is well absorbed in gastrointestinal tract and predominantly metabolized by cytochrome P4502D6 (CYP2D6). After oral administration of 20 mg twice daily in adults, the C max have been observed in the range of 160-180 ng/ml (0.55-0.62 μM) in CYP2D6 extensive metabolizers and up to 925 ng/ml (3.17 μM) in genetically deficient CYP2D6 metabolizers (Sauer et al, 2003). In our in vitro studies, atomoxetine proved to be the most potent P-glycoprotein inhibitor of all the tested agents potentially utilized to treat ADHD.…”
Section: Discussionmentioning
confidence: 78%
“…Atomoxetine, a potent and selective inhibitor of the presynaptic norepinephrine transporter, is used clinically for the treatment of attention-deficit hyperactivity disorder in children and adults (Newcorn et al, 2005). In humans, atomoxetine undergoes extensive metabolism of 4-hydroxylation by CYP2D6 to form 4-hydroxyatomoxetine and is also transformed into a minor metabolite, N-demethylatomoxetine, mainly by CYP2C19 (Ring et al, 2002;Sauer et al, 2003). The enzyme kinetics of CYP2D6.1, CYP2D6.10, and CYP2D6.17 variants toward atomoxetine 4-hydroxylation were characterized, and the results indicated that CYP2D6.10 and CYP2D6.17 exhibited enzyme efficiency (as CL int ), which was 8.58 and 21.9% of CYP2D6.1.…”
Section: Resultsmentioning
confidence: 99%
“…Another example that showed a similar pattern was atomoxetine, which is metabolized by CYP2D6 (aromatic 4-hydroxylation, major pathway in CYP2D6 EM) and CYP2C19 (N-demethylation) (Sauer et al, 2005). In CYP2D6 EM subjects, 4-OH atomoxetine glucuronide constitutes the major circulating moiety, while the plasma AUC ratios of N-desmethyl atomoxetine and 4-hydroxyatomoxetine to parent were low (,0.1) (Sauer et al, 2003). Moreover, in CYP2D6 PM, the AUC ratio of N-desmethyl atomoxetine to parent drug was 0.33 to 0.42 (Sauer et al, 2003;FDA Clinical Pharmacology Review: http:// www.accessdata.fda.gov/drugsatfda_docs/nda/2002/21-411_Strattera_ biopharmr_P2.pdf), thus constituting a moiety that needs to be considered for assessment for potential DDI under the current EMA and draft FDA Guidance.…”
Section: Special Considerations Genetic Polymorphismsmentioning
confidence: 99%
“…In CYP2D6 EM subjects, 4-OH atomoxetine glucuronide constitutes the major circulating moiety, while the plasma AUC ratios of N-desmethyl atomoxetine and 4-hydroxyatomoxetine to parent were low (,0.1) (Sauer et al, 2003). Moreover, in CYP2D6 PM, the AUC ratio of N-desmethyl atomoxetine to parent drug was 0.33 to 0.42 (Sauer et al, 2003;FDA Clinical Pharmacology Review: http:// www.accessdata.fda.gov/drugsatfda_docs/nda/2002/21-411_Strattera_ biopharmr_P2.pdf), thus constituting a moiety that needs to be considered for assessment for potential DDI under the current EMA and draft FDA Guidance. These examples highlight the need to evaluate the abundance of circulating metabolites in relation to the genotype and phenotype of the metabolizing enzymes, if genetic polymorphisms are known to exist for the particular enzyme of interest.…”
Section: Special Considerations Genetic Polymorphismsmentioning
confidence: 99%